Теоретичні підходи до обґрунтування сутності національних фінансових систем в умовах європейської інтеграції - Кулай, Аліна Василівна; Гром, Василь Андрійович; Kulaj, A. V.; Grom, V. A. (Східноєвропейський національний університет ім. Лесі Українки, 2015)
Мета наукової статті – дослідження та обґрунтування сутності національних фінансових систем в умовах європейської інтеграції з використанням системного підходу й аналізу наявних досліджень. Вивчення цього питання дасть можливість узагальнити та обґрунтувати єдині підходи до розуміння сутності національних фінансових систем. In the article we have discovered scientific and theoretic bases of justifying the nature of national financial systems in conditions of European integration. It is also analyzed the establishing and the main stages of developing the integrated European model of the united financial system of the EU, its correlations with national financial systems of the member-countries and countries of the European vector of development. Different points of view of national and foreign scientists were generalized, that allows to give the widen interpretation of the nature of national financial system as a complex of financial relations, financial markets, an institutional part, leverages and instruments, that make the main part of the state economic policy and integrational union. It is justified the correlations of national financial systems with international and united regional systems, their influence onto forming proper economic policies, that are oriented to the modern tendencies of the development of world`s commodity, labor and financial markets. Regarding different points of view of scientists in the field of international economy and practical financiers, we have defined the main directions of reforming the financial system of Ukraine concerning eurointegrational vector of development
Theoretical Approaches to Justifying the Nature of National Financial Systems in Conditions of European Integration.
Keywords: національні фінансові системи; фінансові відносини; ринки; механізми; інструменти; Україна; Європейський Союз; national financial system; financial relations; markets; mechanisms; instruments; Ukraine; the European Union